National Health Service : You must decide (circular) - Bayly, M.B. ; Welply, Alfred ; Crawford, Alexander; Hefferman, L. W.
1948-01 1948 1940s 1 page W128 Telephones Telegrams: MUSEUM 5626-7-8 UFFABRINI, WESTCENT, LONDON. Medical Practitioners' Union General Secretary: ALFRED WELPLY, M.D. 55 & 56, Russell Square, London, W.C.1. January, 1948. NATIONAL HEALTH SERVICE YOU must decide Dear Sir (or Madam), In this letter we do not propose to deal with the many details that divide our profession. We are a responsible body and our object in sending you this letter is to help you to put the proposed change in focus and to determine your action upon rational and liberal lines. THE UNION EXISTS TO HELP THE PROFESSION A few simple questions and answers will make our present position clear and may help to clarify yours. IS CHANGE INEVITABLE? YES — because :— Parliament has passed the National Health Service Act. The people welcome it. The profession recognises its need. No political party dare support its postponement. IS CHANGE FAIR TO THE DOCTOR ? YES — because :— The figure for compensation has been agreed to by the profession. The rate of remuneration approximates to that recommended by the Spens Report. The measure of control is the minimum to which the Treasury would ever consent. IS CHANGE NEEDED ? YES — because :— Everyone sooner or later needs medical treatment. That treatment should not depend upon charity, flag days or recommendations. Social security demands social responsibility. It is the logical extension of the present incomplete service. WHAT WILL CHANGE GIVE THE PATIENT ? A complete health service. A unified and co-ordinated hospital service. Freedom from financial worry during illness. Freedom to choose own doctor. WHAT WILL CHANGE GIVE YOU ? The opportunity to exercise your profession freely. The right to advise any treatment you consider necessary. An administrative framework in which you have a part. A negotiating machinery to which all grievances can be brought. A fair market value for your proprietory interest. A rate of remuneration which, if not generous, is reasonable and sure. A pensionable right which protects, not only yourself, but your wife. WHAT SHOULD YOU DO ? Say that you propose to join the service. Join the service on the appointed day. Advise everyone you know, colleague or patient, to join. If you have any lingering doubts or personal difficulties write us in full and we will do our best to help you. With the co-operation of the profession in operating and perfecting it, the National Health Service Act can bring inestimable benefit to the profession and to the community. Yours faithfully, L. W. Hefferman, President. M. B. Bayly, Vice-President. Alfred Welply, General Secretary. Alexander Crawford, Assistant Secretary. 292/847/5/126